The role of ethical leadership in bullying workplace behaviors: Field research - An Applied Research in The College of Osol Aldeen University (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:                The current research aims to determine the importance of the role and impact of ethical leadership on workplace bullying. The research problem revolves around a significant question: "Why has workplace bullying expanded among employees?" To explain the relationship between the key research variables, two main hypotheses were formulated, from which sub-hypotheses were derived.To achieve the research objectives, a descriptive-analytical approach was used to investigate the opinions of a sample of employees working at the College of Religious Sciences at the university. The sample included 55 employees out of a total population of 80 employees. The purposive sampling method was employed, and their opinions were collected through a structured questionnaire. The data were analyzed using the SPSS and Excel software, and statistical methods such as the Spearman correlation coefficient and simple linear regression were applied.The research concluded several findings, including the influence of ethical leadership on organizational bullying in the studied college. Moreover, there was a statistically significant and inversely proportional relationship between ethical leadership and organizational bullying.